2021
DOI: 10.3390/membranes11080563
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Sulfonated Graphene Oxide-Doped Polymeric Membranes with Improved Anti-Biofouling Behavior

Abstract: In this study, cellulose acetate (CA) was blended with sulfonated graphene oxide (SGO) nanomaterials to endow a nanocomposite membrane for wastewater treatment with improved hydrophilicity and anti-biofouling behavior. The phase inversion method was employed for membrane fabrication using tetrahydrofuran (THF) as the solvent. The characteristics of CA-SGO-doped membranes were investigated through thermal analysis, contact angle, SEM, FTIR, and anti-biofouling property. Results indicated that anti-biofouling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Among all the techniques for this purpose, nanofiltration technique plays the largest role. This technology is generally used in wastewater treatment methods because of its low-cost and effective process [5][6][7]. Generally, most polymeric nanofiltration membranes possess flexibility and low cost; however, they have some major issues, such as poor chemical resistance, restricted life period, and fouling of the membrane [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among all the techniques for this purpose, nanofiltration technique plays the largest role. This technology is generally used in wastewater treatment methods because of its low-cost and effective process [5][6][7]. Generally, most polymeric nanofiltration membranes possess flexibility and low cost; however, they have some major issues, such as poor chemical resistance, restricted life period, and fouling of the membrane [8].…”
Section: Introductionmentioning
confidence: 99%
“…Similar effect of ZnO has been reported in literature when ZnO content was increased in cellulose/ZnO, an increase in contact angle and improvement in hydrophobic character was observed in them 42 . On the other hand, addition of SGO (Sulphonated Graphene Oxide) in CA/SGO composite membrane improved hydrophilic character and exhibited in the form of regular decrease in contact angle [ 49 ]. In these GO/ZnO membranes, the concentration of GO was increased with the decrease in ZnO so both synergized the hydrophilic ability of these membranes.…”
Section: Resultsmentioning
confidence: 99%
“…This consequence is consistent with previous research results, illustrating that nanographene can eliminate hydrophobicity and promote cell adhesion. 47 , 48 This mechanism may contribute to the strong noncovalent bonding ability of graphene and the microtopography of the composite surface. Some studies have indicated that graphene has a strong noncovalent binding ability.…”
Section: Discussionmentioning
confidence: 99%